2015
DOI: 10.3138/cpp.2014-028
|View full text |Cite
|
Sign up to set email alerts
|

Do Immigrants Gain or Lose by Occupational Licensing?

Abstract: This paper studies the effects of occupational licensing in Canada on the earnings of immigrants and non-immigrants. The econometric model is estimated for immigrants and non-immigrants as well as between joiners and leavers from occupationally licensed jobs using a large panel data set. The results suggest that occupational licensing raises wages more for immigrant workers than for non-immigrants with similar observed characteristics. However, the probability of being in an occupationally licensed job is lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Previous Canadian studies use information from the Government of Canada's website, WorkingCanada.org; it not only includes both licensed and certified occupations but also assumes occupations were regulated before the beginning of the data (Banerjee and Phan ; Girard and Smith ; Gomez et al . ). My new occupational licensing indicator is based on a jurisdictional review of occupational statutes and acts, recording the year of occupational licensing laws proclaimed for each occupation across all 10 Canadian provinces.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous Canadian studies use information from the Government of Canada's website, WorkingCanada.org; it not only includes both licensed and certified occupations but also assumes occupations were regulated before the beginning of the data (Banerjee and Phan ; Girard and Smith ; Gomez et al . ). My new occupational licensing indicator is based on a jurisdictional review of occupational statutes and acts, recording the year of occupational licensing laws proclaimed for each occupation across all 10 Canadian provinces.…”
Section: Discussionmentioning
confidence: 97%
“…A limited number of recent studies report that immigrants who work in regulated occupations receive 15 per cent more in wage gains than native born Canadians working in the those occupations, while also receiving the 4 per cent positive wage premiums associated with regulated occupational status (Gomez et al . ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Turning to the costs or side effects of regulation, researchers have found that licensure restricts labour supply and consequently increases both the price of relevant goods and services, and the earnings of regulated practitioners who benefit from the monopoly rents which in many the Canadian and US contexts are observed to be similar in magnitude to those from unionization (e.g., Kleiner 2013, Kleiner and Krueger 2010, Kugler and Sauer 2005, and Gomez et al 2015. Scopes of practice can also be arbitrarily limited by occupational regulation, as particular tasks are assigned to an occupation but restricted from another.…”
Section: The Goals Of Regulationmentioning
confidence: 99%
“…We are aware of no direct evidence regarding trends in the number of regulated/licensed workers in Canada although it is possible, using difficult to compile and limited lists of occupations that are regulated, to track the number of workers in regulated occupations as is done by Gomez et al (2015). However, what is clear is that the regulation of previously unregulated occupations is commonplace -especially in the health sector.…”
Section: Introductionmentioning
confidence: 99%
“…This role places them in a powerful position which given their lack of accountability, can be problematic (E. Girard & Bauder, 2007b;Gomez, Gunderson, Huang, & Zhang, 2015;Hawthorne, 2002). As a result immigrant professionals can experience significant structural barriers (Augustine, 2015b;Ngo & Este, 2006).…”
Section: Recognition Of Overseas Qualificationsmentioning
confidence: 99%